A qualitative review on the impact of enrolment in self-help groups for persons with disabilities in rural Karnataka, India: a comparative study - Regy, Minitta Maria; Shanbhag, Deepthi N. (International Journal Of Community Medicine And Public Health, 2023)
Background: Self-help groups for persons with disabilities exist with a rather common objective to address problems, enhance their strengths, and improve their quality of life. Objectives were to explore the impact of self-help groups on persons with disabilities as a comparative approach among those enrolled in SHG versus those who were not enrolled in the same. Methods: A community-based, qualitative study was done among persons with disabilities in rural Karnataka with a total of 7 focus group discussions, 5 key informant interviews and 2 in depth interviews. Topic guides, recorder and sociogram were used as aids. Themes and sub-themes were formed from the transcript and a deductive analysis was done. Results: A total of 12 villages were covered and the age group of our study participants varied between 18 to 60 years with a mean age of 40.6±12.9 years. Out of the total 97 FGD participants, 36 (37%) males and 14 (14%) females were gainfully employed, out of whom, 12 (33%) males and 8 (57%) females were enrolled in SHGS. Also, 7 (58.3%) out of the 12 males and 5 (62.5%) out of the 8 females had begun their daily means of income post their enrolment in SHGs, thereby accounting for the awareness and efforts to be self-empowered. The KII and IDI were also in alignment with the different perspectives gained from the FGDs, respectively. Conclusions: Self-help groups help improve socialization, and self-esteem of individuals with disability and helps them feel empowered to lead independent lives.